Validation of Molecular Markers Genetically Linked to S-Cytoplasm and Restoration-of-fertility (Rf) Loci in Hot Pepper (Capsicum annuum L.) - K K, Jessy Mol; D C, Lakshmana Reddy; Y B , Manoj; K, Madhavi Reddy (Journal of Horticultural Sciences, 2020)
Existence of CGMS system in hot pepper is due to the rearrangements in the mitochondrial genome and is largely used in economized and pure F 1 hybrid seed production around the world. The orf456, a new ORF present at flanking region of the coxII gene at the 3’ end, was distinguished male sterile cytoplasm in hot peppers along with atp6-2gene. In the current study, eighteen pepper genotypes (nine each of A and corresponding B lines) of varied origin were used to validate with two male sterile cytoplasm (S-cytoplasm) specific sequence characterised amplified region (SCAR) markers viz., atp6-2 (875 bp) and orf456 (456 bp) and one restoration-of-fertility (Rf) locus specific marker, CRF (550 bp). The results clearly showed that the presence of CMS-S-cytoplasm and absence of restoration-of-fertility (Rf) gene in the pepper genotypes studied and is comparable with the phenotypic data. In view of the outcomes it has been reasoned that the accessible S and Rf markers available in the public domain are reproducible and can be promptly utilized for marker assisted selection (MAS) in hot pepper crop improvement program.
Keywords: CGMS; Hot pepper; Marker Assisted Selection; Mitochondria; ORF